In situ statistical measurement of local morphology in carbon-epoxy composites using synchrotron X-ray computed tomography. (October 2019) - Rosini, Sebastian; Mavrogordato, Mark N.; Egorova, Olga; Matthews, Emily S.; Jackson, Samuel E.; Mark Spearing, S.; Sinclair, Ian
Abstract: Models are still deficient in accurately reproducing the mechanisms that trigger tensile failure in unidirectional composites, highlighting a lack of direct experimental evidence. In this study, emphasis is given to the identification of connections between local fibre misorientation, packing and Weibull strength distribution in causing tensile failure. Synchrotron Radiation Computed Tomography (SRCT) and automated image processing techniques are adopted to segment individual fibres from loaded carbon fibre coupons. Subtle indications in the misorientation of local damaged sites are assessed in novel statistical detail for systematic differentiation from non-damaged sites. It is observed that the morphology of the surrounding environment of damaged sites statistically differs from that of non-damaged sites, even though locally damaged sites (containing single or coupled breaks) do not exhibit a peculiar fibre packing arrangement. For adjacent coupled breaks, the statistical nature of fibre separation distances is also reported.